Analisis Performa AES Untuk Sekuriti Jaringan Scada Berbasis ATMega16 - Eka Puji Widiyanto (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2017)
SCADA as the backbone for modern sontrol system has been unseparated part of human daily life, from industrial system, powerline, to military system with its global and vast scope. SCADA by nature is not safe, and because of that reason there is a big security hole in every SCADA system that threatens its functionality. To overcome this, security concept must be applied to existing SCADA system in the form on data encryption. AES 128 bit is used as the encryption method on an 8 bit microprocessor AVR ATMEGA16 clocked at 11.0592MHz. Based s to encrypt 16 bytes block of data and requiremon this chip, AES executed with total time of 40 s for decryption. With this performance on an 8 bit chip architecture, using AES asm60 encryption for any field object in SCADA system is very advisable to achieve higher security level.